Analysing Poedak Application Efficiency in Rural Population Administration: Menganalisis Efektivitas Aplikasi Poedak dalam Administrasi Kependudukan Pedesaan - Santoso, Arif Budy; Riyadh, Ahmad (Universitas Muhammadiyah Sidoarjo, 2023)
This study investigates the efficacy of the Poedak application in population administration services within Karangandong village, utilizing a descriptive qualitative approach. Employing purposive sampling, primary and secondary data were collected via observation, interviews, document abstracts, and recordings. Results indicate Poedak's effectiveness through four key indicators: precision in program objectives, successful program dissemination, alignment with program goals, and program monitoring. The findings reveal commendable precision in program targeting, robust program dissemination through online media and direct community engagement, goal congruence with Gresik Regency's expectations, and effective program monitoring. However, challenges such as limited village-level Poedak awareness among residents and server connectivity issues in Karangandong Village hindered its seamless operation, impeding the application's effectiveness. This study underscores the need for enhanced community awareness initiatives and robust technological infrastructure to optimize the Poedak application's effectiveness in rural population administration. Highlights: Technological Impact: The study assesses the efficacy of the Poedak application in rural administrative services, shedding light on its technological impact on population documentation and management. Challenges in Implementation: It highlights connectivity issues and limited community awareness as pivotal challenges hampering the seamless operation of the Poedak application in rural settings. Need for Enhanced Awareness: Emphasizes the significance of community-oriented awareness programs to bolster the adoption and effectiveness of technological solutions like Poedak in rural administration. Keywords: Poedak application, rural administration, effectiveness, challenges, community awareness